Pembentukan Karakter Siswa Dengan Menerapkan Kebiasaan Unggah-Ungguh Yogyakarta Di Sekolah Dasar - Farinda Khasanah; Maria Margaretha; Salisa Rizky Candra; Beny Lukitoaji (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
The rapid development of 21st-century technology has brought both positive and negative impacts on the behavior of young generations. One of the negative effects is the decline in character education among elementary school students, marked by impolite behavior, lack of respect, and excessive dependence on technology. To address this issue, the application of unggah-ungguh, a Javanese cultural value system, can serve as an effort to build students' character. This study aims to describe the concept of unggah-ungguh, identify its practices in elementary schools, and examine its role and effectiveness in character formation. The research method used is a literature review by analyzing books, journals, scientific articles, and relevant previous studies. The results show that character education based on unggah-ungguh, such as tata krama (politeness), lembah manah (humility), andhap asor (respectfulness), tepa slira (tolerance), grapyak (friendliness), and ewuh-pekewuh (consideration), successfully fosters students’ courtesy, respect, and social awareness. Practices in SD Negeri Jetisharjo and SD Negeri Pleret Lor have proven that integrating unggah-ungguh values creates a harmonious learning environment and nurtures students’ cultural identity. Collaboration between schools, parents, and communities is essential for the success of culturally-based character education.